Sosiologi Komunikasi Masyarakat Industri - Muzzammil, Faisal (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka Palembang, 2021)
This study on the sociology of communication in industrial society is motivated by the heterogeneity and complexity of the social and cultural diversity of the employees of PT Indorama Synthetics Tbk Purwakarta. With the background of the social and cultural diversity of the employees, the purpose of this study is to identify and describe the following two things: First, the social system of industrial society; Second, the communication pattern of industrial society. This study is based on the theory of Gemeinschaft & Gesellschaft from Ferdinand Tonies and Primary & Secondary Communication from Onong Uchjana Effendy. This study belongs to the type of qualitative research with case study methods and subjective approaches. Data collection in this study was carried out by means of observation and interviews. Based on the results of the analysis of the data collected, two important findings were obtained, namely: First, the social system of industrial society is Gesselschaft; Second, the communication pattern of industrial society is primary communication. The results of this study are expected to contribute to the development of the study of the sociology of communication. The results of this study are recommended for sociology academics, communication practitioners, and researchers who are interested in the study of the sociology of communication, as a basic reference and practical guide in further researching industrial societies and similar groups of people. Keywords: Sociology of Communication, Social Systems, Communication Patterns, Industrial Society